SIRT2 inhibition as the Achilles’ heel of ATRX-deficient gliomas - Turcan, S̨evin (Neuro-Oncology, 2024)
ATRX is a chromatin remodeling protein that facilitates H3.3 deposition at telomeres and pericentromeric heterochromatin. It is essential for normal brain development, and mutations in ATRX cause alpha thalassemia X-linked intellectual disability (ATR-X) syndrome, a disorder characterized by severe cognitive defects.1 In pediatric high-grade gliomas, recurrent loss-of-function mutations in ATRX are frequently reported with TP53 and H3F3A mutations.2 In adult gliomas, ATRX is mutated in astrocytomas, co-occurring with IDH1 and TP53 mutations, and in high-grade astrocytomas with piloid features, a recently described molecular class of IDH-wildtype glioma.3 Furthermore, ATRX-deficient tumors exhibit a distinct molecular landscape where telomere length is maintained in a telomerase-independent manner, known as alternative lengthening of telomeres (ALT).4
Veröffentlicht: 06 November 2023
Gesehen am 12.01.2024